(untitled) (Bangladesh Journal of Botany, 2021)
The soil nutrient content, particle size composition, crop yield and erosion resistance were studied considering the slope farmland with different slope sizes and different crops as the research object. The results showed that the available phosphorus content was higher under the wheat planting mode. Rape planting was conducive to the accumulation of organic matter, total nitrogen and available potassium, and nutrient accumulation was more obvious when treated at 5° slope. The soil texture was sandy loam under the wheat planting mode. After rapeseed planting, the soil texture began to change to silt loam. The crop yield was the highest under different planting modes at 5°. Rapeseed was found to increase the soil erosion resistance of sloping farmland compared with wheat, and the greater was the slope, the stronger the erosion resistance. Bangladesh J. Bot. 50(3): 925-932, 2021 (September) Special